Registration of Five Pima Cotton Germplasm Lines (Pima SJ‐FR05–Pima SJ‐FR09) with Improved Resistance to Fusarium Wilt Race 4 and Good Lint Yield and Fiber Quality. Issue 2 (11th March 2016) - Ulloa, Mauricio; Hutmacher, Robert B.; Percy, Richard; Wright, Steven D.; Burke, John
Abstract : Five pima ( Gossypium barbadense L.) cotton germplasm lines—Pima SJ‐FR05 (Reg. No. GP‐1000, PI 675557), Pima SJ‐FR06 (Reg. No. GP‐1001, PI 675558), Pima SJ‐FR07 (Reg. No. GP‐1002, PI 675559), Pima SJ‐FR08 (Reg. No. GP‐1003, PI 675560), and Pima SJ‐FR09 (Reg. No. GP‐1004, PI 675561)— were developed by the USDA‐ARS and jointly released with the University of California in 2015. The primary purpose for these releases is to provide germplasm with good levels of resistance to Fusarium wilt, caused by Fusarium oxysporum f. sp. vasinfectum (FOV) race 4, to cotton breeders. The Pima SJ‐FR05–SJ‐FR09 series originated from the cross of 'Pima S‐6' and germplasm line 89590 in 1999 at the USDA‐ARS in Maricopa, AZ. Pima S‐6 possesses a major gene(s) for FOV race 4 resistance. Initially, the Pima SJ‐FR05–SJ‐FR09 lines were developed from the F2 to F6 from a single seed‐plant descendant. In 2006, a recurrent selection was applied for each line in fields infested with FOV race 4 at two locations in California. In subsequent field and greenhouse tests, the Pima SJ‐FR05–SJ‐FR09 lines showed good resistance to FOV race 4 and good lint yield and fiber quality when compared to 'Phytogen 800', the San Joaquin Valley pima cotton standard. The Pima SJ‐FR05–SJ‐FR09 series will broaden the genetic base of resistance, which is critical to the success and future of the pima cotton industry.